Legal Provisions for Settlement of Plagiarism of Digital Fiction Works - Shodiq, Ja'far; Suisno; Winanda, Susi (Jurnal Independent, 2024)
ABSTRACT Advances in technology and information have a significant impact on the world of writing. The existence of digital platforms makes the world of writing easier to access and enjoy. The convenience felt has positive and negative impacts. The positive impact is that writers can share with other writers to obtain contemporary and modern works. The negative impact is that the vastness of the digital era makes the work that has been produced vulnerable to plagiarism. Plagiarists will find it very easy to copy and paste the work and re-upload the work as if it were the result of the perpetrator's own thoughts. This research is a normative legal research, with a statute approach and a concept approach. The legal materials used are primary legal materials in the form of Laws and Regulations in force in Indonesia. The results of the study can be concluded that: first, Legal provisions for perpetrators of plagiarism of fictional works on digital platforms can be resolved through the courts and outside the courts. Settlement of plagiarism disputes through the courts can be resolved in commercial courts, district courts and administratively. Settlement of plagiarism disputes that are resolved outside the court can be through negotiation, mediation, conciliation and arbitration